Micro‐injection molding of CNT nanocomposites obtained via compounding process. Issue 2 (4th June 2015) - Bongiorno, Alessandro; Pagano, Claudia; Baldi, Francesco; Bellantone, Vincenzo; Surace, Rossella; Fassi, Irene
Abstract : Many research efforts have gone in the production of carbon nanotubes (CNT) composites for functional and structural applications and many processing methodologies have been experimented. Twin‐screw extrusion appears to be the most suitable way from the perspective of production scale up and commercialization of these composites. At the same time, micro‐injection molding process is considered as the key manufacturing technology for the mass production of miniaturized components and devices. Despite the massive literature about nanocomposites and microinjection molding process, few articles focus on the interaction between the compounding process and the following micro‐injection molding transformation processes. This article aims at analyzing the influence of the screw configuration used in compounding process on the rheological and technological properties of the resulting nanocomposites. Two different combinations of screw elements have been tested to incorporate CNTs in two different resins: LCP (liquid crystal polymer) and POM (polyoxymethylene) typically used in micro‐injection molding. The effects of the process set up have been observed studying first the rheology and then the moldability of nano‐compounds microinjected ribs with high aspect ratio. The nanofiller dispersion has been evaluated via light and transmission electron microscopy. The results confirm that, the screws show different capacity at promoting the dispersion of the nanofiller, which affects the moldability of micro‐injected CNT nanocomposites. The viscosity of the polymer seems a critical factor as well, because it influences first the dispersion of CNT bundle during extrusion and then the injection moldability of the composites in the micro‐channels. POLYM. COMPOS., 38:349–362, 2017. © 2015 Society of Plastics Engineers